1994
DOI: 10.1108/01443579410072364
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Personal Computers in Operations Management Education

Abstract: The pervasiveness of personal computers (PCs) in business has encouraged expanded use in business schools. This effort has spawned a multitude of "supplemental" problem-solving software packages, which are frequently offered as peripherals to existing textbooks and are designed for use in the PC enhanced environment [1]. Although the incorporation of computers in education increases realism and facilitates computation, there are divergent views on the extent to which their use enhances learning [2] and little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Therefore, in the teaching-learning environment that was designed, both methodologies (OSC and CADL) were shown to be equally effective in helping students to pass the assessment tests that were done. These results are in keeping with other comparative studies on ICT-based business teaching in which no significant differences have been found in examination scores based on the method used (Coye and Stonebraker, 1994;Friday et al, 2006;McCray, 2000;McLaren, 2004; Interactive learning in OM Merril and Galbraith, 2009). Bearing in mind the findings connected with these objective learning outcomes, it can be stated that the use of the interactive software is an option that is just as effective as the OSC-based teaching in small groups for learning OM and, therefore, that it represents a real alternative to the latter in this discipline.…”
Section: Final Acquired Knowledge Testssupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, in the teaching-learning environment that was designed, both methodologies (OSC and CADL) were shown to be equally effective in helping students to pass the assessment tests that were done. These results are in keeping with other comparative studies on ICT-based business teaching in which no significant differences have been found in examination scores based on the method used (Coye and Stonebraker, 1994;Friday et al, 2006;McCray, 2000;McLaren, 2004; Interactive learning in OM Merril and Galbraith, 2009). Bearing in mind the findings connected with these objective learning outcomes, it can be stated that the use of the interactive software is an option that is just as effective as the OSC-based teaching in small groups for learning OM and, therefore, that it represents a real alternative to the latter in this discipline.…”
Section: Final Acquired Knowledge Testssupporting
confidence: 90%
“…As on the professional level MRP/ERP systems are essentially ICT tools in OM, it might be expected that they could be adapted for ICT-based teaching, and this has been confirmed in this study. Coye and Stonebraker (1994) state that OM is one of the business subjects that is most amenable to CAL and highlight that some subjects -MRP, aggregate scheduling and forecastingcould benefit especially from this type of learning. Meanwhile, Arbaugh et al (2010) state that a growing interest in some OM-related topics such as quality management can Interactive learning in OM be detected in online and blended learning environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers who put these claims forward carried out their researches under conditions of insufficient hardware and software. Finally, various data has shown that there is not a considerable difference between traditional teaching and CAT (Coye and Stonebraker, 1994). These kinds of differences are often encountered in educational researches.…”
Section: Resultsmentioning
confidence: 99%
“…In effect, the computer provides an opportunity for developing countries to leapfrog into the industrial age, and become active players in the new global economy. In addition, the widespread use of CAPM systems will also have a beneficial effect on improving the operations management knowledge base of managers, as simulation packages and sensitivity analysis programmes will force the managers to look at issues in a methodological manner (Coye and Stonebraker, 1994;Goonatilake, 1989b;Southern, 1986).…”
Section: Problems Of Developing Country Enterprisesmentioning
confidence: 99%